1998
DOI: 10.1007/s001340050645
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous dilatational tracheostomy — early results and long-term outcome of 326 critically ill patients

Abstract: When performed by experienced physicians, percutaneous dilatational tracheostomy under fiberoptic guidance is a safe method. The risks of early complications and of clinically relevant tracheal stenoses are low. Subclinical tracheal stenoses are found in about 40% of patients following PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
4
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 33 publications
3
79
4
5
Order By: Relevance
“…Walz et al 16 identified 141 patients who were successfully decannulated of 326 patients who had PDT at seven intensive care units in Germany. One hundred six patients were evaluated with coronal and sagittal plane tracheal radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Walz et al 16 identified 141 patients who were successfully decannulated of 326 patients who had PDT at seven intensive care units in Germany. One hundred six patients were evaluated with coronal and sagittal plane tracheal radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who survive their critical illness or injury, access to long-term follow-up is often difficult because of the complexity of follow-up at tertiary referral centers, persistent medical problems, or a reluctance to return for evaluation by survivors who are asymptomatic. Recent studies to determine the incidence of late complications from PDT have used a variety of methods, including questionnaires, [12][13][14][15] tracheal roentgenograms, 16 tracheal tomograms, 17 magnetic resonance imag-ing, 18 laryngotracheoscopy, 12,13 and various pulmonary function tests. 12,15 The purpose of our study was to determine the incidence of tracheal stenosis and other late complications of PDT in a population of critically ill patients who survived their initial hospital stay and were successfully decannulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two larger trials compared percutaneous tracheostomies with and without broncoscopic guidance and found complication rates of 9.5% and 19%, respectively. [6,7] Because the complication rates associated with fiberoptic bronchoscopic-guided tracheostomies are lower, it is reasonable to use this technique in pediatric patients and even in low-body-weight infants. To the best of our knowledge, our case involved the youngest case with the lowest body weight who has undergone this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The latest tracheostomy cannula with a fallen cuff is placed over the combination of guidewire and guiding catheter. The tracheostomy balloon is inflated (28).…”
Section: Multiple Dilatation Methods (Ciaglia's Technique)mentioning
confidence: 99%